Main principles of training in telecommunications at NBU - Stefanova, Tereza (Yearbook Telecommunications, 2015)
Quality education must be the most important thing for the future engineers. The education in telecommunications at NBU must offer students not only wide knowledge, but also good habits and skills. The realization of education demands such an organization of study processes, in which the basic knowledge, skills and habits make a solid system and can be readily used for studying skills. The principles of educating in telecommunications are strongly connected between them and also help each other. Their using in practice give positive results, the most important of them is the activity of students’ knowledge. On the other hand, not using the principles of education gives a low effectiveness of studying process.